Pengaruh Fasilitas Belajar Terhadap Minat Belajar Siswa SD Negeri Kutabima 01 - Utami, Maulidya; Riyadi, M. Ilham Rahmani; Azizah, Amalia Nurul (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the influence of school facilities on student learning interest sd negeri kutabima 01. This research method used is a quantitative research method with survey research type. This research was carried out using survey research conducted using non-probability techniques where the researcher then collected data using a questionnaire. The data produced were analyzed using statistical tests, namely simple linear regression tests, namely the T test and determination coefficient (R square). This result of the research entitled the influence of school facilities on student learning interest sd negeri kutabima 01 had a siginificant effect. This can be seen from the average precentage after being given treatment on student’s learning interest, namely 0,019 (p < 0,05). The result of the coefficient of determintation test show that learning facilities explain 26,9% of the varioation in student motivation. This shows that although learning facilities are an important factor, there are other elements that also influence student motivation. However, the adjusted R Square value of 0.228 confirms that learning facilities still make a relevant contribution in this regression model, so this research that providing adequate learning facilities is very inportant in increasing student interest and motivation in the educational environment